Intercultural Communicative Competence in Chinese as a Foreign Language Teaching: Implementation of a Practical Program - Balsas-Urena, Isabel Maria (Sinología hispánica. China Studies Review, 2024)
Abstract: : Intercultural communicative competence is the set of knowledge, attitudes and abilities needed by the participants in order to maintain a successful intercultural communicative encounter. The development of this competence is crucial in higher education, especially in translation degrees, since the future translator will need it in his/her future career. However, translation degrees curricula are more focused on the transmission of encyclopedic knowledge, which might cause problems in the long term, especially for those studying languages with distant communicative cultures, as is the case of Spanish and Chinese. A solution might be an adaptation of the Chinese language curricula, where the development of this competence would be included. To test this hypothesis, during academic years 2020/21 and 2021/22 a pilot program was tested in the Translation and Interpreting Degree of University of Granada, in the Chinese language beginner’s level. Both quantitative and qualitative data were obtained from questionnaires and classroom diaries analyses in action research oriented to understand the viability of this kind of curriculum adaptation.